Bridging Cultures: Integrating Game-based Learning based on Local Wisdom in ELT - Maila Shofyana; Yan Imam Santoso; Madya Giri Aditama; Etrisa Helga Yulianti; Mohammad Andre Wibisana (Tell : Teaching of English Language and Literature Journal, 2024)
The implementation of the Merdeka Curriculum in Indonesia aims to cultivate students who embody the values of Pancasila. However, achieving the profile of Pancasila learners has been challenging due to less meaningful learning experiences that do not cater to diverse student needs. This study explores the potential of Game-Based Learning (GBL) integrated with local wisdom to address these challenges in Batang Regency's high schools and vocational schools. Using a qualitative phenomenological approach, data were collected from 25 teachers through questionnaires, interviews, and observations. The findings reveal that GBL activities, such as traditional game adaptations, folktale integration, cultural role-playing, and local-themed vocabulary and grammar games, significantly enhance student engagement, motivation, and cultural awareness. These activities not only make learning more enjoyable and relevant but also foster the values of Pancasila, promote local culture, and support Batang tourism. The study reveals the importance of providing adequate resources and training for teachers to overcome implementation challenges and suggests future research to explore the long-term impacts and scalability of GBL. By integrating local wisdom into GBL, educators can create a dynamic and inclusive learning environment that aligns with the Merdeka Curriculum's goals and enriches the educational experience in Indonesia.